PENERAPAN PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN MINAT BELAJAR SISWA DALAM PEMBELAJARAN IPA FISIKA KELAS VII SMPN 20 PEKANBARU - Fatimah, Nurul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to determine the increase of students’ learning interest through the implementation of Snowball Throwing learning on the states of matter and density. The research subjects were 38 students in class VII7 SMPN 20 Pekanbaru. The design of this research was a pre-experimental with one group pretest-posttest design. Data collection instruments in this research was students’ interest questionnaire consisting of 34 statements. Data were analyzed with descriptive analysis techniques to see the increase students’ interest from the value of gain normalization. The results showed students’ interest with a score of 0.35 on a predicate medium. It can be concluded that the application of Snowball Throwing learning effective to increase students’ learning interest on the subject matter states of matter and density in class VII SMPN 20 Pekanbaru.Key Words: Learning Interest, Snowball Throwing Learning